Peranan UNICEF Dalam Menangani Masalah Tentara Anak di Afrika Tengah Tahun 2007-2012 - Desi Winarti; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research identifies the role of UNICEF in dealing with child soldiers in the Central African country. The research also explains in detail the root causes of conflict and the consequences of the conflict occurred in the Central African country. UNICEF as one of the world institutions that fight for children's rights, has made many changes, working with communities and influencing governments. in Central Africa. UNICEF has provided significant funding to build facilities for the protection of child victims of conflict in central Africa. UNICEF also strive to connect and engage all parties to the conflict to not use children as soldiers as well as the target of violence. Protection and legal training for actors involved in the legal handling of the child. UNICEF has also been working with the African Union regional institutions UN agencies monitor violations.Keywords: UNICEF, Central Africa, child soldiers.